Fertility preservation in the pediatric population—experience from a German Cryobank for ovarian tissue - Baston-Büst, Dunja M.; Bielfeld, Alexandra P. (Frontiers in Endocrinology, 2022)
Counseling children on the possibility of fertility preservation prior to a gonadotoxic treatment supports the decision-making process, taking into account that the patients are in a very vulnerable and mentally exhausting situation following the diagnosis. Referral to specialists can be optimized on-site by routing slips with contact addresses, phone numbers, and mail contacts; available time slots for consultation; possibly offers for cost coverage; and an easy-to-understand information leaflet about the different options available. Some of the options for fertility preservation in the prepubertal population especially are still experimental. The unique possibility of fertility preservation before the onset of the gonadotoxic therapy, which may cause premature ovarian insufficiency or azoospermia in the future, should be highlighted.